Coaching Leadership Behaviours in Strength and Conditioning Coaching: Preferences of NCAA Division I and II Collegiate Student-Athletes Based on Level of Competition - Severiano Tiberi; Jeremy Moody; George Jennings; Steve Cooper; Joseph I. Esformes (International Universities Strength and Conditioning Association, 2024)
This study explored collegiate student-athletesˈ preferences of coaching leadership behaviours in strength and conditioning coaching, evaluating differences between the preferences of coaching leadership behaviours based on the level of competition. A total of 145 National Collegiate Athletic Association student-athletes (Division I = 77, Division II = 68), aged 18-25 years, with a mean = 3 (SD = ±1) strength and conditioning sessions per week, participated. Participants completed an electronic questionnaire involving the athletesˈ preference version of the Revised Leadership Scale for Strength and Conditioning. Summary statistics outlined that the most preferred behaviour was 'training and instruction', median = 4.5 (IQR = 1.0), whilst the least preferred was ˈautocraticˈ, median = 2.0 (IQR = 0.5). Similar results were observed for both Division I and II groups. No statistically significant differences were identified between groups. Effect sizes indicated that the magnitude of differences between groups was small, with the highest value for autocratic behaviour (d = 0.2). The observation of no statistically significant differences between Division I and Division II participants suggests how both levels of competition value similar positive coaching behaviours. This study sheds light on the preferences of coaching behaviours among student-athletes in strength and conditioning coaching. The findings underscore the importance of positive psychosocial behaviours such as training and instruction, positive feedback, situational considerations, and social support for different levels of competition and offer a foundation for further research to explore coaching leadership behaviours in strength and conditioning coaching.